TENDENCIES TO INCREASE THE EFFECTIVENESS OF HISTORY LESSONS - Yusupov Zafar Usmanovich (Journals Park Publishing, 2023)
History is an independent social science that has its place at all stages of education and is important in raising a mature generation. This article discusses how to organize historical education more effectively by analyzing national and foreign literature.
Keywords: effective teaching, history teaching, effective history teaching, method.